Islamic household accounting: romance discussion in accounting curriculum - Krisno Septyan; Iwan Triyuwono; Rosidi Rosidi; Aji Dedi Mulawarman; Achdiar Redy Setiawan (Journal of Islamic Accounting and Finance Research, 2022)
Purpose - This study aims to formulate an Islamic household accounting model that should be part of the accounting curriculum.Method - The method used is grounded theory in constructivism. The first step is self-consciousness, then consideration of participants, followed by data collection, coding, and theory building. Data were collected from 22 informants, 19 of whom were already married whose educational background is in accounting and who were employed in accounting-related positions.Result - The results show that households consider that household accounting needs to be included in the formal accounting curriculum, while most of the heads of the household see it as not mandatory. Discussion revolves around household life, how love springs in the household all the way through, as well as an argument that household accounting must be put as a subject (of curriculum). It is also noted that communication in households must cover both material and spiritual aspects in order to pursue true happiness (a serenity state of a household or sakinah).Implication - Practically, household discussion in classrooms is mandatory for accounting students; this discussion serves as a foothold on how to lead a household life all the way through. Theoretically, for accountants, a household is a life priority in order to shape a better civilization.Originality - This topic of romance in the accounting curriculum has never been specifically addressed in classrooms of undergraduate accounting programs.